THE PROPERLY SUPPORTED GENERALIZED PSEUDO DIFFERENTIAL OPERATORS - Kang, Buhyeon (Journal of the Chungcheong Mathematical Society, 2015)
In this paper, we extend the concept of the pseudo di®erential operators in the usual Schwartz's distribution spaces to the one of the generalized pseudo di®erential operators in the Beurl- ing's generalized distribution spaces. And we shall investigate some properties of the generalized pseudo di®erential operators including the generalized pseudo local property. Finally, we will study the smoothness and properly supported property of these operators. KCI Citation Count: 0